Development and validation of a nomogram model for predicting unfavorable functional outcomes in ischemic stroke patients after acute phase - Yan, Chengjie; Zheng, Yu; Zhang, Xintong; Gong, Chen; Wen, Shibin; Zhu, Yonggang; Jiang, Yujuan; Li, Xipeng; Fu, Gaoyong; Pan, Huaping; Teng, Meiling; Xia, Lingfeng; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction: Prediction of post-stroke functional outcome is important for personalized rehabilitation treatment, we aimed to develop an effective nomogram for predicting long-term unfavorable functional outcomes in ischemic stroke patients after acute phase. Methods: We retrospectively analyzed clinical data, rehabilitation data, and longitudinal follow-up data from ischemic stroke patients who underwent early rehabilitation at multiple centers in China. An unfavorable functional outcome was defined as a modified Rankin Scale (mRS) score of 3-6 at 90 days after onset. Patients were randomly allocated to either a training or test cohort in a ratio of 4:1. Univariate and multivariate logistic regression analyses were used to identify the predictors for the development of a predictive nomogram. The area under the receiver operating characteristic curve (AUC) was used to evaluate predictive ability in both the training and test cohorts. Results: A total of 856 patients (training cohort: n=684; test cohort: n=172) were included in this study. Among them, 518 patients experienced unfavorable outcomes 90 days after ischemic stroke. TOAST classification (p=0.024), antihypertensive agents use (odds ratio [OR]=1.86; p=0.041), 15-day Barthel Index score (OR=0.930; p<0.001) and 15-day mRS score (OR=13.494; p<0.001) were selected as predictors for the unfavorable outcome nomogram. The nomogram model showed good predictive performance in both the training (AUC=0.950) and test cohorts (AUC=0.942). Conclusions: The constructed nomogram model could be a practical tool for predicting unfavorable functional outcomes in ischemic stroke patients underwent early rehabilitation after acute phase.